2004
DOI: 10.1002/ajmg.b.30089
|View full text |Cite
|
Sign up to set email alerts
|

DAT1, DRD4, and DRD5 polymorphisms are not associated with ADHD in Dutch families

Abstract: Recent meta-analyses have indicated that the dopamine transporter gene (DAT1) and the dopamine receptor genes D4 (DRD4) and D5 (DRD5) are associated with attention-deficit hyperactivity disorder (ADHD), although single studies frequently failed to show significant association. In a family-based sample of 236 Dutch children with ADHD, we have investigated the previously described variable number of tandem repeat (VNTR) polymorphisms and two additional microsatellites at the DAT1 and DRD4 loci. DRD5 was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 20 publications
3
28
0
1
Order By: Relevance
“…Many association studies between DRD4 and ADHD have been performed, although results are often controversial. In this regard, although our data in the single-marker analysis are in agreement with previous reports showing no association between ADHD and the 48bpVNTR polymorphism [Roman et al, 2001;Todd et al, 2001;Bakker et al, 2005;Brookes et al, 2005;Carrasco et al, 2006;Johansson et al, 2008;Sonuga-Barke et al, 2008], they are contrary to others having reported on association between the 7R allele and the disorder Faraone et al, 2001;Maher et al, 2002;Wohl et al, 2005;Brookes et al, 2006;Li et al, 2006;Gizer et al, 2008Gizer et al, , 2009Biederman et al, 2009;Langley et al, 2009;Nikolaidis and Gray, 2010]. Likewise, our results for the DRD4 dup120bp polymorphism are in line with most of the literature, including a recent meta-analysis [Barr et al, 2001;Todd et al, 2001;Mill et al, 2003;Kirley et al, 2004;Brookes et al, 2005;Bhaduri et al, 2006;Gizer et al, 2009], but not with findings from the first two association analyses of this variation [McCracken et al, 2000].…”
Section: Discussionsupporting
confidence: 93%
“…Many association studies between DRD4 and ADHD have been performed, although results are often controversial. In this regard, although our data in the single-marker analysis are in agreement with previous reports showing no association between ADHD and the 48bpVNTR polymorphism [Roman et al, 2001;Todd et al, 2001;Bakker et al, 2005;Brookes et al, 2005;Carrasco et al, 2006;Johansson et al, 2008;Sonuga-Barke et al, 2008], they are contrary to others having reported on association between the 7R allele and the disorder Faraone et al, 2001;Maher et al, 2002;Wohl et al, 2005;Brookes et al, 2006;Li et al, 2006;Gizer et al, 2008Gizer et al, , 2009Biederman et al, 2009;Langley et al, 2009;Nikolaidis and Gray, 2010]. Likewise, our results for the DRD4 dup120bp polymorphism are in line with most of the literature, including a recent meta-analysis [Barr et al, 2001;Todd et al, 2001;Mill et al, 2003;Kirley et al, 2004;Brookes et al, 2005;Bhaduri et al, 2006;Gizer et al, 2009], but not with findings from the first two association analyses of this variation [McCracken et al, 2000].…”
Section: Discussionsupporting
confidence: 93%
“…The application of foregoing criteria yielded 30 studies [Cook et al, 1995;Gill et al, 1997;Waldman et al, 1998;Daly et al, 1999;Jiang et al, 1999;Palmer et al, 1999, in Chinese;Holmes et al, 2000;Lunetta et al, 2000;Swanson et al, 2000;Barr et al, 2001;Curran et al, 2001;Roman et al, 2001;Todd et al, 2001;Kirley et al, 2002;CEDAR from Maher et al, 2002;Muglia et al, 2002;Chen et al, 2003;Qian et al, 2003, in Chinese;Hawi et al, 2003;Kustanovich et al, 2004;Qian et al, 2004;Bakker et al, 2005;Bobb et al, 2005;Feng et al, 2005;Langley et al, 2005; Brookes et al [2006] involved two samples so they were included as two independent studies, respectively. Table II gives the odds ratios and their 95% CIs for the 18 TDT studies.…”
Section: Resultsmentioning
confidence: 99%
“…This association has been supported by others, 32,33 but not all studies. [34][35][36] Two meta-analyses showed no significant association (P = 0.21 and P = 0.20) of the 3 0 VNTR with ADHD. 37,38 Importantly, the 5 0 and 3 0 regions of the DAT1 locus are separated by a recombinational 'hot spot' between exons 7 and 9.…”
Section: Introductionmentioning
confidence: 92%